Adult plant response of near-isogenic lines and stocks of wheat carrying specific Lr genes against leaf rust - M.K. MENON2, S.M.S. TOMAR1 and (Indian Phytopathology, 2002)
Near-isogenic lines and stocks of common wheat carrying specific Lr genes were screened for adult plant resistance against leaf rust (Puccinia recondita f. sp. triticl) pathotypes prevailing in the Nilgiris (South India) under natural and artificial epiphytotic conditions for a period of 10 years (1985-1995). AI;en genes, namely, Lr9, Lr19, Lr14, Lr25, Lr28, Lr32 and Lr37 conferred a high degree of adult plant resistance (APR), while Lr18, Lr21, Lr22a, Lr35 and Lr36 exhibited moderate resistance to leaf rust. However, wheats carrying LrUb, Lr31 + Lr27 and Lr34 conditioned moderate susceptibility. Gene Lr26 from SecaJe cereale and Agropyron elongatum-derived gene Lr29 were ineffective. Adult plant response of these stocks against stem and stripe rusts was also recorded. The backcross improved lines carrying genes Lr19 and Lr14 also showed APR to leaf rust.